An inverse diffusion problem with nonlocal boundary conditions - Ismailov, Mansur I.; Ogur, Bulent (Wiley, 2016)
This article considers the inverse problem of identification of a time-dependent thermal diffusivity together with the temperature in an one-dimensional heat equation with nonlocal boundary and integral overdetermination conditions when a heat exchange takes place across boundary of the material. The well-posedness of the problem is studied under some regularity, and consistency conditions on the data of the problem together with the nonnegativity condition on the Fourier coefficients of the initial data and source term. The inverse problem is also studied numerically by using the Crank-Nicolson finite difference scheme combined with predictor-corrector technique. The numerical examples are presented and discussed. (c) 2015 Wiley Periodicals, Inc. Numer Methods Partial Differential Eq 32: 564-590, 2016
Keywords: inverse problem; heat equation; diffusion coefficient; nonlocal boundary conditions; generalized Fourier method; finite difference method